PENINGKATAN PENGETAHUAN KADER STUNTING DI WILAYAH BINAAN PUSKESMAS BRINGIN MELALUI EDUKASI BERBASIS DIGITAL DENGAN METODE BRAINSTORMING DI ERA GLOBALISASI DALAM PENCEGAHAN STUNTING - Devi Pramita Sari Devi; Nur Hikmah; Fifi Anisa Nur Hidayati; Alifah Sari Nugraini (P3M Universitas Aisyiyah Surakarta, 2023)
Stunting is a condition of failure to grow to achieve normal growth due to poor nutritional status in a long period of time. In the preliminary study, there were 5 children under two who were stunted at the Bringin Health Center and it was found that there was a lack of training and knowledge of cadres related to stunting. PkM participants are Stunting Cadres assisted by Bringin Community Health Center. The purpose of this PkM activity is to increase the knowledge of stunting cadres through digital-based education with the brainstorming method in stunting prevention. This is the basis for conducting community service with the title